A Sociology of Translation and the Central Role of the Translator. Issue 3 (December 2016) - Berneking, Steve
Translation studies scholars have recently recognized a definitive "social" turn in the field, leading to the emergence of a sociology of translation which recognizes that translation happens in the mind of translators as social beings who function in multiple roles and negotiate meanings, situated within an environment of social and cultural dimensions. A sociology of translation shifts the focus from texts to the translators, their roles, social networks, and lasting effects on society. In this paper, I review some recent discussions in translation studies, focusing specifically on the emergence of a sociology of translation. My purpose is to explore how we might reaffirm the competing social networks within which the Bible translator works and within which Bible translation is carried out. A sociology of translation, I argue, helps us become more aware of the central role of the translators as socially constructed and constructive agents, simultaneously producing texts and making meaning.